Pengaruh Penerapan Model Pembelajaran Project Based Learning (PjBL) terhadap Hasil Belajar IPAS pada Peserta Didik Kelas IV SD Negeri 17 Pontianak Kota - Retno Diah Palupi; Hery Kresnadi; Rio Pranata (Departement of Mathematics Education, 2024)
This study aims to analyze the effect of the application of the Project Based Learning (PjBL) learning model on the learning outcomes of IPAS in class IV students of SD Negeri 17 Pontianak Kota. The population of this study were all fourth grade students of SD Negeri 17 Pontianak Kota, totaling 65 students. The sampling technique in this study was nonprobability sampling technique with saturated sampling type, where all population members were sampled. The data collection technique used was measurement technique/test in the form of multiple choice questions. The results of this study indicate that there is a significant difference in the learning outcomes of IPAS groups of experimental and control class students. Based on data analysis, the average value of the experimental class post-test was 87.25 while the average value of the control class post-test was 80. Based on the results of the t test calculation, obtained tcount = 7.976219 and ttable = 2.039513 which means tcount > ttable, then Ha is accepted, proving that there is an effect of applying the Project Based Learning (PjBL) learning model on IPAS learning outcomes. Based on the results of the effect size (ES) calculation, ES = 0.63 was obtained, which is included in the medium category. Thus, it can be concluded that the application of the Project Based Learning (PjBL) learning model has a positive influence on the learning outcomes of IPAS in class IV students of SD Negeri 17 Pontianak Kota.